2001
DOI: 10.1021/ic001298x
|View full text |Cite
|
Sign up to set email alerts
|

Time-Resolved Optical and Infrared Spectral Studies of Intermediates Generated by Photolysis of trans-RhCl(CO)(PR3)2. Roles Played in the Photocatalytic Activation of Hydrocarbons1

Abstract: Described are picosecond and nanosecond time-resolved optical (TRO) spectral and nanosecond time-resolved infrared (TRIR) spectral studies of intermediates generated when the rhodium(I) complexes trans-RhCl(CO)L2 (L = PPh3 (I), P(p-tolyl)3 (II), or PMe3 (III)) are subjected to photoexcitation. Each of these species, which are precursors in the photocatalytic activation of hydrocarbons, undergoes CO labilization to form an intermediate concluded to be the solvated complex RhCl(Sol)L2 (A(i)). The picosecond stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
29
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 55 publications
5
29
0
Order By: Relevance
“…Both cis and trans isomers for the 14-electron RhCl(PR3)2 intermediate may adopt either a singlet or a triplet configuration and either spin state is predicted to be lower in energy depending on the computational method used. [55][56][57][58][59] Correlated methods, however, favor a singlet ground state in better agreement with the experimental results. Clearly, great care must be exercised in the selection of the computational technique for the investigation of two-state reactivity.…”
Section: <Figure 8>supporting
confidence: 69%
“…Both cis and trans isomers for the 14-electron RhCl(PR3)2 intermediate may adopt either a singlet or a triplet configuration and either spin state is predicted to be lower in energy depending on the computational method used. [55][56][57][58][59] Correlated methods, however, favor a singlet ground state in better agreement with the experimental results. Clearly, great care must be exercised in the selection of the computational technique for the investigation of two-state reactivity.…”
Section: <Figure 8>supporting
confidence: 69%
“…[16][17][18][19][20] This assignment can be confirmed by a similar experiment with deuterated n-[D 18 ]octane in which a new band at ñ = 1466 cm À1 was observed that results from n(Rh III ÀD) vibrations in addition to the bands at ñ = 1963 and 1985 cm À1 , whereas the band at ñ = 2065 cm À1 was absent ( Figure S2). [16][17][18][19][20] This assignment can be confirmed by a similar experiment with deuterated n-[D 18 ]octane in which a new band at ñ = 1466 cm À1 was observed that results from n(Rh III ÀD) vibrations in addition to the bands at ñ = 1963 and 1985 cm À1 , whereas the band at ñ = 2065 cm À1 was absent ( Figure S2).…”
Section: Spectroscopic Investigations and Reaction Mechanismsupporting
confidence: 66%
“…After 10 min, two new bands appear simultaneously at ñ = 1986 and 2065 cm À1 , which can be assigned to the n(Rh III ÀCO) and n(Rh III ÀH) modes, respectively. [16][17][18][19][20] This assignment can be confirmed by a similar experiment with deuterated n-[D 18 ]octane in which a new band at ñ = 1466 cm À1 was observed that results from n(Rh III ÀD) vibrations in addition to the bands at ñ = 1963 and 1985 cm À1 , whereas the band at ñ = 2065 cm À1 was absent ( Figure S2). Alternatively, these bands might stem from two different intermediate Rh complexes that contain either CO or H as the ligand (vide infra).…”
Section: Spectroscopic Investigations and Reaction Mechanismsupporting
confidence: 66%
“…We studied this reaction first with the conventional flash system, 52 then later using laser flash photolysis. 53 In benzene solution, this substrate undergoes reversible photo-dissociation of CO ( Scheme 4 , k CO = 7.8 × 10 8 M –1 s –1 ). By carrying out the experiment in the presence of reactants such as PPh 3 , H 2 and ethylene, it was possible to determine other second order rate constants for trapping the Rh(PPh 3 ) 2 Cl intermediate.…”
Section: Flash Photolysis Probes Of Reactive Intermediatesmentioning
confidence: 99%
“…For example, the k L for the reaction with PPh 3 was determined to be ∼6 × 10 7 M –1 s –1 in 296 K benzene while that with H 2 was nearly a factor of 30 slower. In addition, k CO values in cyclohexane and dichloromethane were ∼2-fold and 5-fold lower, respectively, suggesting that the intermediate is not three-coordinate, but is weakly bound by solvent in the position vacated by CO. 53 …”
Section: Flash Photolysis Probes Of Reactive Intermediatesmentioning
confidence: 99%